Effectiveness of an Educational Intervention (Based on BASNEF Model) on lifestyle of patients with heart failure - Masumeh Hemmati Maslakpak; Seide Zahra Merghati; Alireza Didarloo (Payesh, 2017)
Objective (s): Healthy lifestyle is an important factor to reduce the incidence, severity and complications of diseases. BASNEF model, as an educational framework, in addition to patients’ knowledge and attitude considers environment and social norms in changing behavior. This study aimed to assess the effectiveness of an educational intervention based on BASNEF model on lifestyle of patients with heart failure. Methods: In this quasi-experimental study, 60 patients with heart failure were enrolled in the study and allocated to intervention and control groups (30 per each group). The intervention group revived 4 sessions based BASNEF while the control group received nothing. To collect data participants completed a lifestyle and BASNED model questionnaires at two points in time: at baseline and 3 months follow-up. Data analysis was performed using descriptive and inferential statistics. Results: The mean scores of total lifestyle did not differ between the two groups after the intervention (p=0.16), However some aspects of lifestyle such as nutrition, sleep patterns, physical health, stress and tobacco use were significantly differed between the two groups (p<0.05). The analysis of data also showed that the mean scores of BASNEF structures before and after intervention significantly differed in intervention group (p<0.0001). Conclusion: The findings suggest that an educational intervention based on BASNEF might have some positive effect on lifestyle of patients with heat failure.